Perancangan Dan Pembuatan Alat Bantu PencekamanUntuk Mesin Mortiser - Muhammad, Agung, Eko Setiawan, ST., MT., Ph.D (2016)
The technology that growing rapidly increasing custom product demand. On the other hand, support the technology mostly has limitations in operation. This resulted in an inability to accommodate overall the technology needs and the impact on the delay of the manufacturing process. In the production process Industrial Engineering Design Practice 1 at the Industrial Engineering Department, Muhammadiyah University of Surakarta, where one production machine that Mortiser machine can not be used optimally because of the size of the workpiece to be processed is not ideal for existing clamping system. This prompted the researchers to make modifications to the clamping system. Modifications made by considering the dimensions of the workpiece to be processed, the process is done by machines Mortiser, the technical aspects of designing production tools, as well as the availability of tools and material support. Tools designed clamping expected to overcome problems Mortiser machining process on the machine, allowing the machine operator to run the machining process, and increase efficiency.